Gastric adenocarcinoma burden and late‐stage diagnosis in Latino and non‐Latino populations in the United States and Texas, during 2004–2016: A multilevel analysis - Dorothy Long Parma; Susanne Schmidt; Edgar Muñoz; Amelie G. Ramirez (Cancer Medicine, 2021)
Abstract Background Gastric cancer disproportionately affects Latinos, but little is known about regional effects and risk factors. We compared primary incidence, late‐stage diagnosis, and risk factors for gastric adenocarcinoma (GCA) from 2004 to 2016 in Latinos and non‐Latinos in the United States, Texas (TX), and South Texas (STX). Methods We collected case data from Surveillance, Epidemiology, and End Results (SEER) and the Texas Cancer Registry. We generated average annual age‐adjusted incidence rates, rate ratios (RRs), and 95% confidence intervals (CIs) using SEER*Stat software and analyzed the cases by anatomic site, demographics, and county‐level risk factors using SAS 9.4. We constructed multilevel logistic regression models for late‐stage GCA, adjusting for patient‐ and county‐level characteristics. Results Latinos had higher overall GCA incidence rates in all regions, with the greatest disparities in overlap GCA in STX males (RR 4.39; 95% CI: 2.85, 6.93). There were no differences in cardia GCA rates for non‐Hispanic Whites (NHWs) and Latino women in all regions. Younger patients, patients with overlapping or not otherwise specified (NOS) lesions, and patients diagnosed during 2012–2016 had higher odds of late‐stage GCA. The stratification by location showed no differences in late‐stage disease between NHWs and Latinos. The stratification by anatomic site showed Latinos with cardia GCA were more likely to have late‐stage GCA than NHWs (OR: 1.13, p = 0.008). At the county level, higher odds of late‐stage GCA were associated with medium and high social deprivation levels in TX without STX (OR: 1.25 and 1.20, p = 0.007 and 0.028, respectively), and medium social deprivation index (SDI) in patients with NOS GCA (OR: 1.21, p = 0.01). Conclusions STX Latinos experience greater GCA disparities than those in TX and the United States. Younger age and social deprivation increase the risk for late‐stage GCA, while Latinos and women are at higher risk specifically for late‐stage cardia GCA. There is a need for population‐specific, culturally responsive intervention and prevention measures, and additional research to elucidate contributing risk factors.